Anti-fouling catalytic membrane based on interface hydrophilicity induction and preparation method and application thereof

By introducing CoAl-LDH and Ti3C2Tx coupling structures into the PVDF membrane matrix, the interfacial hydrophilic induction technology is used to solve the problems of membrane pore blockage and hydrophobicity limiting anti-fouling performance, and the effect of efficient removal of organic pollutants in water is achieved.

CN119186273BActive Publication Date: 2025-03-18HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411675840.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-18
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

During the water treatment process, existing membranes are prone to blockage of membrane pores due to pollutant deposition and adsorption, resulting in irreversible pollution, and the hydrophobicity of conventional PVDF membranes limits its anti-pollution performance.

Method used

By introducing layered bimetallic hydroxide (CoAl-LDH) and Ti3C2Tx coupled structures into the PVDF membrane matrix, a heterogeneous catalytic film is formed, and the membrane's anti-pollution performance is improved using interfacial hydrophilicity induction technology.

Benefits of technology

It has achieved a significant improvement in the filtration flux and anti-fouling performance of the membrane under the persulfate oxidation system, enhanced catalytic efficiency and chemical stability, and effectively removed organic pollutants in the water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186273B_ABST
    Figure CN119186273B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of catalytic membrane separation, and specifically discloses an anti-fouling catalytic membrane based on interface hydrophilicity induction, a preparation method and an application thereof. The preparation method comprises: using an etching method to prepare Ti3AlC2 into a layered structure of Ti3C2T x ; Add cobalt salt, aluminum salt and PVP to Ti3C2T x After the dispersion is stirred evenly, a reducing agent is added, and then a heating reaction is carried out to obtain a catalyst; the catalyst is ultrasonically dispersed in an organic solvent, and then PVDF powder is added, and then heated and matured to obtain a casting liquid; the casting liquid is placed in a coagulation bath for wet phase conversion reaction after spinneret molding to obtain an anti-fouling catalytic membrane. The present invention introduces a hydrophilic polymer to construct a stable hydrophilic interface on the bonding surface of PVDF and the catalyst, thereby improving the hydrophilicity of the membrane and enhancing the chemical stability of the catalyst in the organic phase. Thereby, the self-cleaning function of the membrane is realized under the persulfate system, and the anti-fouling performance of the membrane is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalytic membrane separation, and in particular relates to an anti-fouling catalytic membrane based on interface hydrophilicity induction, a preparation method and an application thereof. Background Art

[0002] The successful application of membrane filtration technology in water treatment has been proven to be an effective technology, but the membrane fouling problem generated during the application process has always been a pain point that plagues its practical application. How to effectively alleviate the irreversible pollution caused by membrane pore blockage is a key issue that needs to be solved urgently.

[0003] Current research shows that giving the membrane catalytic oxidation function is beneficial to alleviating membrane pollution, which aims to screen pollutants through membrane pores and take advantage of spatial confinement to improve its catalytic performance and anti-fouling performance. Therefore, the rational design of catalytic membranes with micro-nano materials and micro-nano structures can produce membranes with excellent catalytic and anti-fouling properties.

[0004] Conventional PVDF (polyvinylidene fluoride) membranes are prone to depositing and adsorbing pollutants due to their inherent hydrophobicity, which limits their practical applications. Introducing hydrophilic catalysts into the membrane matrix is ​​considered a feasible method for developing anti-fouling catalytic membranes, which mainly involves depositing a hydrophilic layer on the surface of the membrane matrix. However, due to the lack of stable chemical bonds between the hydrophilic catalyst and the PVDF membrane matrix, the hydrophilic layer is prone to fall off during use.

[0005] Layered double hydroxide (LDH) contains a large number of hydrophilic groups -OH, which is a typical catalyst. The interlayer ion interchangeability and metal oxygen bridge transfer limit the electron-hole recombination. In particular, the active groups on its surface not only make it easy to combine with other semiconductor materials, but also provide a good interface to promote the occurrence of AOP (advanced oxidation) reactions. Ti3C2T x There are abundant terminal functional groups -OH, -O, and -F in Ti3C2T, which can bind tightly to LDH and form stable chemical bonds with the membrane matrix material. x Coupling to form heterostructures is a promising strategy. Summary of the invention

[0006] The purpose of the present invention is to provide an anti-fouling catalytic membrane based on interface hydrophilicity induction, a preparation method and an application thereof, aiming to improve the catalytic efficiency and anti-fouling performance of the anti-fouling catalytic membrane by adjusting the interface hydrophilicity.

[0007] To achieve the above object, the present invention adopts the following technical solutions:

[0008] The method for preparing an anti-fouling catalytic membrane based on interface hydrophilicity induction comprises the following steps:

[0009] (1) Ti3AlC2 is made into a layered structure of Ti3C2T by etching x ;

[0010] (2) Add cobalt salt, aluminum salt and PVP (polyvinyl pyrrolidone) to Ti3C2T x After the dispersion is stirred evenly, a reducing agent is added, and then a heating reaction is performed to obtain the catalyst CoAl-LDH / Ti3C2T x ;

[0011] (3) Catalyst CoAl-LDH / Ti3C2T x Ultrasonic dispersion in an organic solvent, adding PVDF powder, and then heating and maturing to obtain a casting solution;

[0012] (4) The casting liquid is placed in a coagulation bath after being spun into a spinneret for wet phase transformation reaction. The catalyst CoAl-LDH / Ti3C2T x It is doped into PVDF and forms a hydrophilic layer at the interface between the two to obtain an anti-fouling catalytic membrane.

[0013] In a further solution, in step (1), Ti3C2T x The thickness is 10 to 30 μm;

[0014] The etching method in the present invention is a known method, specifically, Ti3AlC2 is ultrasonically dispersed in an etchant, and etching is performed at 60-80°C for 36-48h.

[0015] In a further embodiment, the etchant is at least one of hydrochloric acid, sodium fluoride solution, hydrofluoric acid solution, and ammonium fluoride solution.

[0016] Further solution, in step (2), Ti3C2T x The dispersion is Ti3C2T x Ultrasonic dispersion in pure water or deionized water, where Ti3C2T x The concentration is 0.5g / 100mL;

[0017] The molar ratio of the cobalt salt to the aluminum salt is 1:1, and the molar ratio of the reducing agent to the cobalt salt is 1 to 1.5:1; PVP and Ti3C2T x The mass ratio is 1:0.2~0.4.

[0018] In a further embodiment, the cobalt salt in step (2) is one of cobalt nitrate, cobalt acetate, cobalt chloride and hydrates thereof;

[0019] The aluminum salt is one of aluminum nitrate, aluminum chloride, aluminum sulfate and hydrates thereof;

[0020] The reducing agent is urea or hydrazine hydrate.

[0021] In a further embodiment, the heating reaction temperature in step (2) is 90-95° C. and the time is 10-12 h;

[0022] The product after heating reaction was washed and dried to obtain the catalyst CoAl-LDH / Ti3C2T x .

[0023] In a further embodiment, the organic solvent in step (3) is DMAC (dimethylacetamide), DMF (dimethylformamide) or NMP (N-methylpyrrolidone); all of which are conventional organic solvents in the art.

[0024] The catalyst CoAl-LDH / Ti3C2T x The mass percentage of is 0.05-0.5%, and the mass percentage of PVDF powder is 15-20%;

[0025] The heating and aging is carried out by heating in a sealed oil bath at 75-85° C. for 8-12 hours.

[0026] In a further embodiment, in step (4), the coagulation bath is formed by dissolving a hydrophilic polymer in pure water or deionized water;

[0027] The temperature of the coagulation bath is 20-30° C., and the time of the wet phase conversion reaction is 1-5 minutes.

[0028] In a further embodiment, the mass percentage of the hydrophilic polymer in the coagulation bath is 1 to 5%;

[0029] The hydrophilic polymer is at least one of dopamine monomer, acrylic acid or acrylamide.

[0030] The second object of the present invention is to provide an anti-fouling catalytic membrane obtained by the above preparation method, wherein the anti-fouling catalytic membrane is a hollow fiber microfiltration membrane with a membrane pore size of 0.1 to 0.4 μm.

[0031] The third invention objective of the present invention is to provide the application of the above anti-fouling catalytic membrane, which is used for removing organic pollutants in water under a persulfate oxidation system.

[0032] In a further solution, the removal rate of the organic pollutants is 85% to 90%, and the operating flux is stable at 15 to 20 L / m 2 ·h.

[0033] In the present invention, the casting solution is extruded through a spinneret to prepare a fiber membrane, wherein the spinneret can be a hollow fiber membrane spinning nozzle as disclosed in CN106521654A.

[0034] In the present invention, the casting liquid is placed in a coagulation bath after being spun and formed, wherein the hydrophilic polymer enters the PVDF matrix through phase separation, and the catalyst CoAl-LDH / Ti3C2T x The polymerization occurred under the induction of the catalyst CoAl-LDH / Ti3C2T x It is doped in PVDF and forms a hydrophilic layer at the interface between the two, that is, it is transformed into an anti-fouling catalytic membrane CoAl-LDH / Ti3C2T through solvent-nonsolvent wet phase transformation. x @PVDF.

[0035] The present invention has the following beneficial effects:

[0036] (1) This application uses an etching method to make Ti3AlC2 into a layered structure of Ti3C2T x , while the layered Ti3C2T x It is a two-dimensional layered material. By removing the Al layer through etching, it can form a heterojunction structure with metal materials, which is more conducive to electron transfer. Secondly, this interlayer confinement structure accelerates the collision frequency between active oxygen species and pollutants, which is conducive to the decomposition of organic pollutants.

[0037] (2) The present invention introduces a hydrophilic polymer into PVDF and the catalyst CoAl-LDH / Ti3C2T x The combined surface constructs a stable hydrophilic interface, improves the hydrophilicity of the membrane, and enhances the chemical stability of the catalyst in the organic phase, so that the prepared membrane can achieve the self-cleaning function of the membrane in the persulfate system and enhance its anti-fouling performance.

[0038] (3) The present invention anchors the CoAl-LDH layered structure regularly and directional on the Ti3C2T x On the surface of the film, positive and negative charged nanosheets form a three-dimensional structure, construct an asymmetric nano-ion transmission channel, enhance the electron transmission capacity, improve the electrochemical performance of the material and improve its catalytic efficiency. And by introducing a new catalyst CoAl-LDH / Ti3C2T x , which prompts the hydrophilic polymer to enter the casting solution and induce its polymerization during the PVDF phase separation process, regulates the catalyst to segregate to the surface, constructs a hydrophilic interface between the catalyst and the PVDF matrix, produces a more solid and stable anchoring site in the membrane matrix, and enhances the hydrophilicity of the membrane.

[0039] (4) Since the layered double hydroxide (CoAl-LDH) contains a large number of hydrophilic groups -OH, the interchangeability of its interlayer ions and the transfer of metal oxygen bridges limit the electron-hole recombination, thereby improving its catalytic efficiency. In particular, the active groups on its surface not only make it easy to combine with other semiconductor materials, but also provide a good interface to promote the occurrence of AOP (advanced oxidation) reactions. Ti3C2Tx There are abundant terminal functional groups -OH, -O, and -F in the CoAl-LDH, which can bind tightly to LDH and form stable chemical bonds with the membrane matrix material. x The coupling forms a heterostructure to form an asymmetric nano-ion transport channel, enhance the electron transport capacity and improve the catalytic efficiency.

[0040] (5) The purpose of adding PVP (polyvinyl pyrrolidone) when preparing the catalyst in this application is to better adhere aluminum ions and cobalt ions to Ti3C2T x The purpose of adding reducing agent is to produce LDH.

[0041] Therefore, the anti-fouling catalytic membrane prepared by the present invention induces a catalytic membrane-like Fenton reaction under the PMS system, and oxidatively degrades tetracycline as a target pollutant under the PMS system, which has good anti-fouling performance and stability. It can also remove organic pollutants such as bisphenol A, rhodamine B, and perfluorooctanoic acid in water. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The Ti3C2T prepared in Example 1 x And the electron microscope (SEM) image of the raw material Ti3AlC2, where a is the electron microscope image of Ti3AlC2, and b is the SEM image of Ti3C2T x Electron microscope image of .

[0043] Figure 2 The catalyst CoAl-LDH / Ti3C2T prepared in Example 1 x Transmission electron microscope (TEM) images, where a is the TEM full view and b is the TEM high-resolution image.

[0044] Figure 3 The catalyst CoAl-LDH / Ti3C2T prepared in Example 1 x X-ray diffraction (XRD) and Fourier transform infrared spectrometer (FT-IR) spectra, where a is the XRD graph and b is the FT-IR graph.

[0045] Figure 4 These are SEM images of the anti-fouling catalytic membrane in Example 1, where a is a full SEM image and b is a cross-sectional image.

[0046] Figure 5 The anti-fouling performance of the anti-fouling catalytic membrane and the pure PVDF membrane in Example 1 is characterized, wherein a is the pollutant index and b is a graph showing the change in permeation flux over time. DETAILED DESCRIPTION

[0047] The present invention is further described below in conjunction with specific examples, but the essence of the present invention is not limited to the following examples. The methods are conventional methods unless otherwise specified, and the materials can be obtained from public commercial channels unless otherwise specified. Those skilled in the art should know that any simple transformation or substitution based on the essence of the present invention belongs to the protection scope claimed by the present invention.

[0048] The organic pollutants in the present invention refer to tetracycline, bisphenol A, rhodamine B, perfluorooctanoic acid, etc., and the persulfates include potassium persulfate, sodium persulfate, and ammonium persulfate. In the following embodiments, the organic pollutant is tetracycline, and the persulfate is potassium persulfate.

[0049] Embodiment 1:

[0050] (1) Weigh 1g of Ti3AlC2 and place it in 40mL of 50% ammonium fluoride solution. Ultrasonic dispersion for 30min, stirring at 300r / min, reaction temperature 80℃, etching time 36h. Then wash with anhydrous ethanol until impurities are removed to obtain a layered structure Ti3C2T x , and its thickness is 10μm.

[0051] like Figure 1 Ti3AlC2 and Ti3C2T are shown x From Figure b, we can clearly see that Ti3C2T x It is a multi-layered structure.

[0052] (2) 0.5 g of the Ti3C2T prepared above was added x Fully dispersed in 100mL deionized water, then weighed 2.9g cobalt nitrate (0.015mol), 3.3g aluminum nitrate and 2.5g PVP and added to the above dispersion, ultrasonically dispersed evenly, added 0.9g urea (0.015mol), and continued to stir evenly; then transferred to the reactor and reacted in a 90℃ oven for 10h. After the reaction was complete, the product was washed and dried to obtain the catalyst CoAl-LDH / Ti3C2T x .

[0053] from Figure 2 It can be seen that the prepared catalyst CoAl-LDH / Ti3C2T x It is composed of multiple flake LDH grown on the substrate material Ti3C2T x And it has a flower-like structure.

[0054] from Figure 3 The XRD and FT-IR spectra show that the catalyst CoAl-LDH / Ti3C2T x It is composed of CoAl-LDH and Ti3C2Tx Synthetic, because from Figure 3 It is clearly seen in a that CoAl-LDH / Ti3C2T x Ti3C2T appeared x The characteristic diffraction peaks of the (002) crystal plane in CoAl-LDH and the (003) and (006) crystal planes in CoAl-LDH. Figure 3 In b, it can be seen that CoAl-LDH / Ti3C2T x The infrared characteristic peaks of Ti-O, Al-O and Co-O appeared.

[0055] (3) Weigh the catalyst CoAl-LDH / Ti3C2T prepared above x 0.025g was added to 42.5g of DMAC (dimethylacetamide) solution, and ultrasonicated until completely dispersed; then 7.5g of PVDF powder was added, fully dissolved, and sealed and heated in a 75℃ oil bath for 12h, and the liquid was completely matured to a transparent gray-black color to obtain a casting liquid. The doping mass ratio of the catalyst in the casting liquid was 0.05%.

[0056] (4) Weigh 10 g of dopamine monomer and dissolve it in 1 kg of pure water to make a coagulation bath. Heat it to 20°C and keep the temperature constant.

[0057] (5) The casting liquid is formed by spinning and then put into a coagulation bath, where a wet phase transformation reaction is carried out for 1 min, and then taken out and dried at room temperature to obtain CoAl-LDH / Ti3C2T x @PVDF anti-fouling catalytic membrane.

[0058] The pore diameter of the spinneret for spin forming in this embodiment is: inner diameter 0.7mm, outer diameter 1.3mm. The inner and outer diameters and membrane pore diameters of the membrane are detected by a mercury intrusion meter. The anti-fouling catalytic membrane is a hollow fiber microfiltration membrane with an inner diameter of 0.7mm and an outer diameter of 1.3mm, and a membrane pore diameter of 0.15μm.

[0059] Its SEM picture is as follows Figure 4 As shown, after the catalyst CoAl-LDH / Ti3C2T x The pores of the doped and modified membrane are more developed and its surface separation layer is denser, which is conducive to the increase of membrane flux.

[0060] Application Example 1:

[0061] The CoAl-LDH / Ti3C2T prepared in Example 1 x @PVDF anti-fouling catalytic membrane is tested for filtration flux. The test method is: immerse the membrane in ultrapure water at a pressure of -0.01Mpa, and measure the ratio of the volume of ultrapure water passing through the membrane per unit time to the surface area of ​​the membrane, in units of L / m 2 ·h.

[0062] Specifically, the pure PVDF membrane and the anti-fouling catalytic membrane prepared in Example 1 were made into a 0.08 m 2 The membrane components were then completely immersed in a 20ppm tetracycline solution. The ends of the membrane components were connected to the water inlet bucket through a silicone tube. The pressure was maintained at -0.01Mpa for 60 minutes. The water production volume of the anti-fouling catalytic membrane was 1.48L and the water production volume of the pure PVDF membrane was 0.96L. Their filtration fluxes were 18.5L / m 2 h, 12L / m 2 ·h.

[0063] The preparation method of the pure PVDF membrane is the same as that in Example 1.

[0064] Compared with the pure PVDF membrane under the same conditions, the anti-fouling catalytic membrane CoAl-LDH / Ti3C2T x @PVDF can significantly increase its filtration flux, that is, its filtration flux decay slows down; and reduces irreversible pollution ( DR ir ) index is 3.7, so it has anti-fouling advantages, such as Figure 5 shown.

[0065] The anti-fouling catalytic membrane was immersed in the wastewater containing the organic pollutant tetracycline under the persulfate oxidation system. The anti-fouling catalytic membrane had a relatively excellent tetracycline removal efficiency, and its anti-fouling index was significantly improved compared with the pure PVDF membrane. The concentration of tetracycline was tested by UV-visible spectrophotometry.

[0066] The anti-fouling performance of the anti-fouling catalytic membrane is calculated by the following formulas:

[0067]

[0068]

[0069]

[0070]

[0071] In the above formula, is the initial filtration flux recovered after one or more filtrations, is the initial flux, is the filtration flux at a certain moment during the period, FRR is the flux recovery rate, DR t (%) is the total pollution index, DR r (%) is the reversible pollution index, DR ir (%) is the irreversible pollution index.

[0072] The preparation process of organic pollutant tetracycline wastewater under the persulfate oxidation system is as follows:

[0073] Take 0.3g of potassium persulfate and dissolve it in 1L of ultrapure water, then add 0.02g of tetracycline and mix evenly. The concentration of persulfate in the wastewater is 0.3g / L and the initial concentration of tetracycline is 20mg / L.

[0074] The water was discharged under negative pressure suction of -0.01Mpa and operated for 60 minutes. The concentration of tetracycline in the effluent was tested by UV-visible spectrophotometry and was 2.4mg / L, indicating that the removal rate of tetracycline was 88%.

[0075] Embodiment 2:

[0076] (1) Weigh 1g Ti3AlC2 powder and place it in 40mL of 50% hydrofluoric acid solution for ultrasonic dispersion for 30min. Stir at a rate of 300r / min, reaction temperature 70℃, and etch for 42h. Then wash with anhydrous ethanol until the impurities are removed to prepare a layered Ti3C2T x , and its thickness is 20μm.

[0077] (2) Weigh the Ti3C2T prepared above x 0.5g of the mixture was fully dispersed in 100mL of pure water, 2.37g (0.01mol) of cobalt chloride hexahydrate and 3.75g (0.01mol) of aluminum nitrate nonahydrate were weighed and ultrasonically dispersed in the above dispersion, and then 2g of PVP and 0.75g (0.015mol) of hydrazine hydrate as a reducing agent were added and stirred evenly; then the mixture was transferred to a reactor and reacted in an oven at 92°C for 11h. After the reaction was complete, the product was washed and dried to obtain the catalyst CoAl-LDH / Ti3C2T x .

[0078] (3) Weigh 0.1 g of the catalyst prepared above and add it to 41.5 g of DMF solution, and perform ultrasonic treatment until it is completely dispersed. Then add 8.5 g of PVDF powder and heat it in an oil bath at 80 °C for 10 h. When the liquid is matured to a gray-black transparent state, a casting liquid is obtained. The doping mass ratio of the catalyst in the casting liquid is 0.2%.

[0079] (4) Weigh 20 g of acrylamide monomer and dissolve it in 1 kg of pure water to make a coagulation bath. Heat it to 25°C and keep the temperature constant.

[0080] (5) After the casting liquid is formed by spinneret, it is immersed in a coagulation bath for wet phase inversion reaction for 2 minutes to obtain an anti-fouling catalytic membrane.

[0081] The aperture of the spinneret for spin forming in this embodiment is: inner diameter 0.7mm, outer diameter 1.3mm. The inner and outer diameters and membrane pore diameters of the membrane are measured by mercury intrusion meter. The inner diameter of the anti-fouling catalytic membrane is 0.7mm, the outer diameter is 1.3mm, and the membrane pore diameter is 0.25μm.

[0082] Application Example 2:

[0083] Similar to Application Example 1, the anti-fouling catalytic membrane prepared in Example 2 was subjected to a filtration flux test:

[0084] The pressure was maintained at -0.01 MPa for 60 min, and the water production volume was 1.51 L. The filtration flux of the anti-fouling catalytic membrane was 18.87 L / m 2 ·h.

[0085] Compared with pure PVDF membrane prepared under the same conditions, its filtration flux is 13.13L / m 2 h, indicating that the anti-fouling catalytic membrane prepared by the present invention generates active oxygen species under PMS to decompose pollutants, alleviate membrane pore and surface pollution, and improve filtration flux.

[0086] In addition, the anti-fouling catalytic membrane prepared in Example 2 was immersed in the wastewater containing tetracycline, an organic pollutant, in the persulfate oxidation system of Application Example 1, and the water was discharged under negative pressure suction of -0.01 MPa. The membrane was operated for 60 minutes. The concentration of tetracycline in the effluent was tested by UV-visible spectrophotometry and found to be 2.7 mg / L, indicating a tetracycline removal rate of 86.5%.

[0087] Embodiment 3:

[0088] (1) Weigh 1g Ti3AlC2 powder and place it in 40mL of 50% sodium fluoride solution for ultrasonic dispersion for 30min, and react at a stirring rate of 300r / min and a reaction temperature of 60℃ for 48h. Wash with anhydrous ethanol until the impurities are removed to prepare a layered Ti3C2T x , and its thickness is 30μm.

[0089] (2) Weigh the Ti3C2T prepared above x 0.5g was fully dispersed in 100mL deionized water, 2.49g (0.01mol) cobalt acetate tetrahydrate and 3.75g (0.01mol) aluminum nitrate nonahydrate were weighed and ultrasonically dispersed in the above dispersion, and then 1.25g PVP and 0.75g (0.015mol) of hydrazine hydrate as a reducing agent were added and stirred evenly; then the mixture was transferred to a reactor and reacted in an oven at 95℃ for 12h. After the reaction was complete, the product was washed and dried to obtain the catalyst CoAl-LDH / Ti3C2T x .

[0090] (3) Weigh 0.25 g of the catalyst prepared above and add it to 40 g of NMP solution, and perform ultrasonic treatment until it is completely dispersed. Then add 10 g of PVDF powder, stir and dissolve thoroughly, and heat in an oil bath at 85 °C for 8 h. When the liquid is matured to a gray-black transparent state, a casting liquid is obtained. The doping mass ratio of the catalyst in the casting liquid is 0.5%.

[0091] (4) Weigh 50 g of acrylic acid monomer and dissolve it in 1 kg of deionized water to prepare a coagulation bath. Heat it to 30°C and keep the temperature constant.

[0092] (5) After the casting liquid is formed by spinneret, it is immersed in a coagulation bath for wet phase inversion reaction for 5 minutes to obtain an anti-fouling catalytic membrane.

[0093] The aperture of the spinneret for spin forming in this embodiment is: inner diameter 0.7mm, outer diameter 1.3mm. The inner and outer diameters and membrane pore diameters of the membrane are measured by mercury intrusion meter. The anti-fouling catalytic membrane has an inner diameter of 0.7mm, an outer diameter of 1.3mm, and a membrane pore diameter of 0.4μm.

[0094] Application Example 3:

[0095] Similar to Application Example 1, the filtration flux test was performed on the anti-fouling catalytic membrane prepared in Example 3:

[0096] The pressure was maintained at -0.01 MPa for 60 min, and the water production volume was 1.59 L. The filtration flux of the anti-fouling catalytic membrane was 19.75 L / m 2 ·h.

[0097] Compared with pure PVDF membrane prepared under the same conditions, its filtration flux is 13.75L / m 2 h, illustrating the anti-fouling catalytic membrane CoAl-LDH / Ti3C2T prepared by the present invention x @PVDF improves its filtration flux.

[0098] In addition, the anti-fouling catalytic membrane prepared in Example 3 was immersed in the wastewater containing tetracycline, an organic pollutant, in the persulfate oxidation system of Application Example 1, and the water was discharged under negative pressure suction of -0.01 MPa. The membrane was operated for 60 minutes and the concentration of tetracycline in the effluent was tested by UV-visible spectrophotometry to be 2.3 mg / L, indicating that the tetracycline removal rate was 88.5%.

[0099] Comparative Example 1:

[0100] The preparation method is the same as in Example 1, except that:

[0101] The catalyst CoAl-LDH / Ti3C2T was not doped during the preparation of the membrane. x , other conditions are the same. Specifically:

[0102] (1) Add 8g of PVDF powder, fully dissolve it, and heat it in a sealed oil bath at 75℃ for 12h. When the liquid is completely matured to a transparent gray-black color, a casting liquid is obtained. The doping mass ratio of the catalyst in the casting liquid is 0%.

[0103] (2) Weigh 10 g of dopamine monomer and dissolve it in 1 kg of pure water to make a coagulation bath. Heat it to 20°C and keep the temperature constant.

[0104] (3) The casting liquid is injected into a coagulation bath after spinneret molding, and a wet phase inversion reaction is carried out in the coagulation bath for 1 minute. The liquid is then taken out and dried at room temperature to obtain a PVDF membrane.

[0105] As in Application Example 1, the PVDF membrane prepared in Comparative Example 1 was immersed in the wastewater containing tetracycline, an organic pollutant, in the persulfate oxidation system of Application Example 1, and the water was discharged under a negative pressure suction of -0.01Mpa. After running for 60 minutes, the concentration of tetracycline in the effluent was tested by UV-visible spectrophotometry and was 9.7mg / L, with a tetracycline removal rate of 51.5%. This indicates that the PVDF membrane has a low removal rate for tetracycline. In addition, its irreversible pollution ( DR ir ) value is 13.7, which means that the anti-fouling property is also significantly reduced.

[0106] Comparative Example 2:

[0107] The preparation method is the same as in Example 1, except for the following two steps:

[0108] (4) Weigh 5 g of dopamine monomer and dissolve it in 1 kg of pure water to make a coagulation bath (the mass concentration of the hydrophilic polymer is 0.5%), heat it to 20°C, and keep the temperature constant;

[0109] (5) After the casting liquid is formed by spinneret, it is immersed in a coagulation bath to carry out a wet phase inversion reaction for 20 seconds to obtain an anti-fouling catalytic membrane.

[0110] The inner and outer diameters and membrane pore diameters were detected by a mercury intrusion meter. The anti-fouling catalytic membrane was a hollow fiber microfiltration membrane with an inner diameter of 0.7 mm and an outer diameter of 1.3 mm, and a membrane pore diameter of 0.15 μm.

[0111] As in Application Example 1, the anti-fouling catalytic membrane prepared in Comparative Example 2 was immersed in the same Application Example 1 wastewater containing tetracycline, an organic pollutant, in a persulfate oxidation system. The tetracycline concentration in the water was detected to be 3.8 mg / L, and the removal rate was 81%. This indicates that the amount of hydrophilic polymer entering the PVDF matrix during the wet phase conversion process of the anti-fouling catalytic membrane is small, and the conversion time is also short, thus causing a slight decrease in catalytic performance. In addition, irreversible pollution ( DR ir ) value is 4.5, and the anti-fouling property is also significantly reduced.

[0112] Comparative Example 3:

[0113] The preparation method is the same as that of Example 1, the only difference being the catalyst preparation process:

[0114] (2) 0.5 g of the Ti3C2T prepared above was added x Fully dispersed in 100 mL of deionized water, 4.5 g of copper nitrate trihydrate and 5 g of urea were weighed and added to the above dispersion, stirred evenly and transferred to a reactor to react in a 90 ° C oven for 10 h. After the reaction was complete, the product was washed and dried to obtain the catalyst Cu2O / Ti3C2T x .

[0115] The membrane prepared in Comparative Example 3 was immersed in the wastewater containing tetracycline, an organic pollutant, in the persulfate oxidation system of Application Example 1, and the water was discharged under negative pressure suction of -0.01Mpa. After running for 60 minutes, the concentration of tetracycline in the effluent was 3.7mg / L as measured by UV-visible spectrophotometry, and the tetracycline removal rate was 81.5%. This shows that the membrane prepared in Comparative Example 3 has a low removal rate for tetracycline. In addition, irreversible pollution ( DR ir ) value is 5.2, and the antifouling property is also significantly reduced. Therefore, the single metal and Ti3C2T x The catalytic effect of the composite heterojunction is slightly lower than that of the bimetallic, especially the unique properties of LDH determine the improvement of membrane performance.

[0116] Comparative Example 4:

[0117] The preparation method is the same as that of Example 1, except that the catalyst is different: the Ti3C2T x As a catalyst.

[0118] The membrane prepared in Comparative Example 4 was immersed in the wastewater containing tetracycline, an organic pollutant, in the persulfate oxidation system of Application Example 1, and the water was discharged under negative pressure suction of -0.01Mpa. After running for 60 minutes, the concentration of tetracycline in the effluent was tested by UV-visible spectrophotometry and found to be 13.2mg / L, with a tetracycline removal rate of 34%. This shows that the membrane prepared in Comparative Example 4 has a low removal rate for tetracycline. In addition, its irreversible pollution ( DR ir ) value is 10.5, and the antifouling property is also significantly reduced. This shows that the pure Ti3C2T x The catalytic ability is very low and the degradation efficiency of pollutants is not high, so the anti-pollution ability is also limited.

[0119] Comparative Example 5:

[0120] The preparation method is the same as that of Example 1, the only difference being the coagulation bath, which in this comparative example is 1 kg of pure water.

[0121] Similar to Application Example 1, the membrane prepared in Comparative Example 5 was subjected to a filtration flux test: water was discharged under a negative pressure suction of -0.01 Mpa, and the operating flux was 15.2 L / m 2 Compared with Example 1, the flux is reduced, mainly because no hydrophilic polymer is added to the coagulation bath, resulting in no significant improvement in the hydrophilicity of the PVDF polymer and no promotion of catalyst segregation to the membrane surface, resulting in the failure to fully develop the finger layer.

[0122] The membrane prepared in Comparative Example 5 was immersed in the wastewater containing tetracycline, an organic pollutant, in the persulfate oxidation system of Application Example 1. The concentration of tetracycline in the effluent was tested by UV-visible spectrophotometry and found to be 3.2 mg / L, with a tetracycline removal rate of 84%. In addition, irreversible pollution ( DR ir ) value is 6.5, and the anti-fouling performance is slightly reduced.

[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an anti-fouling catalytic membrane based on interface hydrophilicity induction, characterized in that: The following steps are involved: (1) Ti3AlC2 is made into a layered structure of Ti3C2T by etching x ; (2) Adding cobalt salt, aluminum salt and PVP to Ti3C2T x After the dispersion is stirred evenly, a reducing agent is added, and then a heating reaction is performed to obtain the catalyst CoAl-LDH / Ti3C2T x ; (3) Catalyst CoAl-LDH / Ti3C2T x Ultrasonic dispersion in an organic solvent, adding PVDF powder, and then heating and maturing to obtain a casting solution; (4) The casting liquid is placed in a coagulation bath after being spun into a spinneret for wet phase transformation reaction. The catalyst CoAl-LDH / Ti3C2T x Doped in PVDF, and forming a hydrophilic layer at the interface between the two, an anti-fouling catalytic membrane is obtained; The coagulation bath is formed by dissolving a hydrophilic polymer in pure water or deionized water, and the hydrophilic polymer is at least one of dopamine monomer, acrylic acid or acrylamide.

2. The preparation method according to claim 1, characterized in that: Ti3C2T in step (1) x The thickness is 10 to 30 μm; The etching method comprises ultrasonically dispersing Ti3AlC2 in an etchant and etching at 60-80°C for 36-48 hours.

3. The preparation method according to claim 2, characterized in that: The etchant is at least one of hydrochloric acid, sodium fluoride solution, hydrofluoric acid solution, and ammonium fluoride solution.

4. The preparation method according to claim 1, characterized in that: Step (2) Ti3C2T x The dispersion is Ti3C2T x Ultrasonic dispersion in pure water or deionized water, where Ti3C2T x The concentration is 0.5g / 100mL; The molar ratio of the cobalt salt to the aluminum salt is 1:1, and the molar ratio of the reducing agent to the cobalt salt is 1 to 1.5:1; PVP and Ti3C2T x The mass ratio is 1:0.2~0.

4.

5. The preparation method according to claim 1, characterized in that: In step (2), the cobalt salt is one of cobalt nitrate, cobalt acetate, cobalt chloride and hydrates thereof; The aluminum salt is one of aluminum nitrate, aluminum chloride, aluminum sulfate and hydrates thereof; The reducing agent is urea or hydrazine hydrate.

6. The preparation method according to claim 1, characterized in that: The heating reaction temperature in step (2) is 90-95°C and the time is 10-12h; The product after heating reaction was washed and dried to obtain the catalyst CoAl-LDH / Ti3C2T x .

7. The preparation method according to claim 1, characterized in that: In step (3), the organic solvent is DMAC, DMF or NMP; The catalyst CoAl-LDH / Ti3C2T x The mass percentage of is 0.05-0.5%, and the mass percentage of PVDF powder is 15-20%; The heating and aging is carried out by heating in a sealed oil bath at 75-85° C. for 8-12 hours.

8. The preparation method according to claim 1, characterized in that: The temperature of the coagulation bath is 20-30° C., and the time of the wet phase conversion reaction is 1-5 minutes.

9. The preparation method according to claim 8, characterized in that: The mass percentage of the hydrophilic polymer in the coagulation bath is 1-5%.

10. The anti-fouling catalytic membrane obtained by the preparation method according to any one of claims 1 to 9, characterized in that: The anti-fouling catalytic membrane is a hollow fiber microfiltration membrane, and the membrane pore size is 0.1-0.4 μm.

11. The use of the anti-fouling catalytic membrane according to claim 10, characterized in that: It is used to remove organic pollutants in water under the persulfate oxidation system.

12. The use according to claim 11, characterized in that: The removal rate of organic pollutants is 85% to 90%, and the operating flux is stable at 15 to 20 L / m 2 ·h.

Citation Information

Patent Citations

  • Hollow fiber membrane spinning nozzle and method for preparing hollow fiber membrane

    CN106521654A

  • Cu2O / MXene-PVDF self-cleaning hybrid membrane as well as preparation method and application thereof

    CN116550154A